The effect of the surface roughness of carbon fibres on CNT growth by floating-catalyst chemical vapour deposition. (2013) - Lee, Geunsung; Kim, Kyoung Ju; Yu, Woong-Ryeol; Youk, Ji Ho
The effect of the surface roughness of a substrate, in particular carbon fibre, on the growth of carbon nanotubes (CNTs) was investigated using floating-catalyst chemical vapour deposition. Carbon fibres (CFs) with four different surface roughness levels were prepared using thermal treatments under an argon and air environment, after which they were used as a substrate for CNT synthesis. The rough surface was observed to be more beneficial to cultivate uniform and long CNTs. By examining the morphologies and chemical components of both CF and CNT-grafted-CF surfaces using electron microscopy, atomic force microscopy, the Brunauer-Emmett-Teller method, and Fourier transform spectroscopy, it was revealed that the surface roughness of the substrate plays an important role in maintaining the activation of catalyst nanoparticles for growing CNTs.